Central and East European Online Library (CEEOL) database, the opportunity to increase the international visibility of USARB researchers (Confluenţe Bibliologice, 2019)
The changes taking place in the world of information require libraries to expand their activities to take on new roles aimed at supporting the research area. In order to increase the quality, impact and international visibility, the USARB Scientiﬁc Library is looking for new ways and tools to promote the research results of Bălţi university professors.
Keywords: databases; periodicals; research